KONDISI SOSIAL EKONOMI PETANI KELAPA SAWIT DI KECAMATAN KINALI KABUPATEN PASAMAN BARAT - Hendra Putra Yulis; Khairani khairani (DEPARTEMEN GEOGRAFI FIS UNP, 2022)
This study aims to determine the socio-economic conditions of oil palm farmers in IndonesiaKinali District, West Pasaman Regency. This research method uses the Mix Method.The population in this study consisted of 369 oil palm farmers in three Nagari in KecamatanKinali are Anam Koto Selatan, Anam Koto Utara and Sigunanti. Samples taken 15% ofThe total population is 56 oil palm farmers who were selected using simple randomsampling (simple random sample). Sources of research data come from oil palm farmers and agenciesrelated. Data collection techniques used are questionnaires, interviews and documentation.The results of this study indicate that the socio-economic conditions of oil palm farmers include the level ofThe average education of a farmer's child is high school graduate, has a permanent house (own) withconcrete floor, oil palm farmers have 3-5 children on average. The average land area of ​​oil palm farmers is 1.791ha, with a production level of 151.2 kg, a selling price of Rp.1300/kg and a monthly income of Rp2,117,500, this result is far lower than usual. Thus it can be concluded thatThe decline in the price of palm oil results in a low level of the economy so that farmers find it difficultto meet the necessities of life.